Utility of fine needle aspiration cytology in metastatic lymph nodes - D Ghartimagar; A Ghosh; S Ranabhat; MK Shrestha; R Narasimhan; OP Talwar (Association of Clinical Pathologists of Nepal, 2011)
Background: Fine needle aspiration cytology is a reliable as well as an inexpensive diagnostic method. It is suitable for the developing countries like Nepal for the diagnosis of lymphadenopathy at any approachable site. Fine needle aspiration cytology not only confirms the presence of metastatic disease but also, in most cases, gives the clue regarding the origin of the primary tumor. The aim of the study was to find out the cytological diagnosis of metastatic lymph node lesions. Materials and Methods: A combined prospective and retrospective study was done of all metastatic lymph node lesions (including both superficial and deep nodes) reported in Department of Pathology, Manipal Teaching Hospital, Pokhara from January 2005 to Deceember 2010. Results: A total of 4180 cases of fine needle aspiration cytology were carried out of which 508 cases were of lymph node. Cytology results were unsatisfactory in 58 specimens (12%), “reactive” or “infective” in 347 specimens (68%), positive for metastasis in 93 specimens (18%) and hematolymphoid malignancies include 10 cases (2%). The most common site was anterior and posterior triangles cervical nodes. The most common malignancy was adenocarcinoma, seen in 62 cases (67%), followed by metastatic squamous cells carcinoma (14 cases, 15%). Conclusion: Fine needle aspiration cytology of lymphadenoathy is a useful tool in diagnosing metastatic lesions with good certainty. Keywords: Fine needle aspiration cytology; Lymphadenopathy; Metastasis DOI: http://dx.doi.org/10.3126/jpn.v1i2.5399 JPN 2011; 1(2): 92-95